Bilateral liquefactive corneal necrosis: a rare and devastating complication of vitamin A deficiency in the adult. Issue 2 (19th February 2021) - Lata, Suman; Bafna, Rahul Kumar; Asif, Mohamed Ibrahime; Sachan, Anusha
Abstract : A 34year-old man presented with diminution of vision, pain and whitish opacity in both eyes (right eye followed by left eye) since 1 week. He is a known case of chronic alcoholic abuse. He had multiple episodes of haemoptysis in the past. On general physical examination, he was severely malnourished with multiple oral ulcers. Visual acuity at presentation was light perception in both eyes with projection of rays accurate in all quadrants. Slit-lamp biomicroscopy revealed bilateral total corneal melt with diffuse conjunctival congestion. Corneal scrapings and blood investigations were done and he was started on empirical topical and systemic therapy followed by surgical intervention, with large corneal grafts in both the eyes (right eye followed by left eye) with 1 day interval. The visual gain in both the eyes were 20/400 at first postoperative day. The right eye developed severe fibrinous reaction on the second postoperative day which resolved with topical antibiotics, topical steroids and systemic steroids. The patient was followed up via telemedicine (due to COVID-19 outbreak) and he is able to carry out his daily routine work independently.